Nepal : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2000)
Nepal has maintained macroeconomic stability under the Poverty Reduction and Growth Facility Arrangement. Executive Directors commended the low inflation, strong macroeconomic stability, and international reserves. They stressed the need to improve fiscal position, enhance private and foreign investment, accelerate project implementation, and strengthen rural infrastructure. They encouraged the authorities to strengthen the efforts in eliminating the weaknesses in the macroeconomic database, reform the banking system, mobilize budgetary revenue, improve fiscal transparency, and tackle problems of governance and corruption.